Noncanonical Constructions in English and How They Work to Package Information - Ikmi Nur Oktavianti (Ahmad Dahlan Journal of English Studies, 2016)
Linguistic construction embodies information that is plausible to be modified in certain context when the speaker wants to emphasize on certain aspect. This is the nature of language users and the construction they produce. Each language is assumed to possess its own various ways of structuring the information spoken or written by the language user. English, for example, which is known as fixed word order language with SVO order has its various ways of structuring the information delivered by the speaker to the interlocutor. Preposing, postposing, and argument reversal are three best ways to indicate which information is prominent in the speaker’s mind so that the hearer will have the same concept as the speaker. Those are included as the alternative ways to construct sentence and propose syntactic choices to the speaker. Information structure has been one of the most intriguing fields of study involving both syntactic and pragmatic analyses. Hence, this paper aims at describing the noncanonical constructions in English and how they work to package information by using the interface of both disciplines.